Does Economic Support Have an Impact on the Health Status of Elderly Patients With Chronic Diseases in China? - Based on CHARLS (2018) Data Research - Tang, Shaoliang; Xu, Yun; Li, Zhengjun; Yang, Tongling; Qian, David (Frontiers in Public Health, 2021)
Abstract Abstract Objective: The economic support of elderly patients with chronic diseases may affect their health status. This study assessed the impact of economic support on the health status of elderly patients with chronic diseases in China and explored the relationship between regional economic differences and the impact of economic support on health status. Methods: This study used the data of 3,416 elderly patients with chronic diseases from the China Health and Retirement Longitudinal Study (CHARLS) in 2018. Logit model and stepwise regression method were used to analyze and compare the influence of economic support on self-rated health, mental health and activities of daily living (ADL) of elderly patients with chronic diseases. Sub-regional comparison was used for the research of regional differences in the impact of economic support on health. Results: we find that economic support has a positive effect on the health status of elderly patients with chronic diseases in China. Socioeconomic support has a positive effect on self-rated health and mental health of elderly patients with chronic diseases, and the effect on activities of daily living (ADL) is no longer significant after the gradual inclusion of control variables. Family economic support has no significant impact on the health dimensions of elderly patients with chronic diseases. with respect to regional differences, socioeconomic support can improve mental health in central China and improve self-rated health in western China, while it can improve overall health status in eastern China. The influence of family economic support on different health dimensions in different regions is still insignificant. Conclusions: The health status of elderly patients with chronic diseases is affected by socioeconomic support in China. In order to improve the health of elderly patients with chronic diseases, it is necessary to increase socioeconomic support. Meanwhile, it is also essential to pay attention to the differences in economic support between different regions and increase the socioeconomic support for elderly patients with chronic diseases in undeveloped regions so as to improve their health status.